TNF alpha is an effective therapeutic target for rheumatoid arthritis. - Feldmann, M; Brennan, F; Elliott, M; Williams, R; Maini, R (1995)
Rheumatoid arthritis is the most common of a number of diseases in which inflammation and tissue destruction is driven by an autoimmune process. Current therapy is inadequate, and this has prompted major research efforts, both in academia and industry, to understand more about the pathogenesis, and hence provide the rationale for new therapeutic strategies. Here we review our studies of cytokine expression and regulation in rheumatoid joints, which has culminated in demonstrating that TNF alpha blockade, using a chimeric (human IgG1/K, mouse Fv) anti-TNF alpha antibody, cA2, markedly ameliorates arthritis. This defines a therapeutic target for rheumatoid arthritis.